2013
DOI: 10.1002/chem.201300463
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional Control of Block Copolymer Nanofibers with a π‐Conjugated Core: Crystallization‐Driven Solution Self‐Assembly of Amphiphilic Poly(3‐hexylthiophene)‐b‐poly(2‐vinylpyridine)

Abstract: With the aim of accessing colloidally stable, fiberlike, π-conjugated nanostructures of controlled length, we have studied the solution self-assembly of two asymmetric crystalline-coil, regioregular poly(3-hexylthiophene)-b-poly(2-vinylpyridine) (P3HT-b-P2VP) diblock copolymers, P3HT23-b-P2VP115 (block ratio=1:5) and P3HT44-b-P2VP115 (block ratio=ca. 1:3). The self-assembly studies were performed under a variety of solvent conditions that were selective for the P2VP block. The block copolymers were prepared by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
135
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 94 publications
(142 citation statements)
references
References 77 publications
5
135
2
Order By: Relevance
“…Although the specific proof of concept example described here involved PFS 30 -b-P2VP 300 as the micelle forming polymer, the fabrication protocol should in principle apply to any BCP that forms elongated core-crystalline micelles and to any substrate to which the corona chains of the seed crystallites can attach. For example, we have recently shown that CDSA can be extended to BCP micelles with a conjugated crystalline polythiophene core 22,37 Electron microscopy. Bright-field transmission electron microscopy (TEM) images were taken using a Hitachi H-7000 instrument.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the specific proof of concept example described here involved PFS 30 -b-P2VP 300 as the micelle forming polymer, the fabrication protocol should in principle apply to any BCP that forms elongated core-crystalline micelles and to any substrate to which the corona chains of the seed crystallites can attach. For example, we have recently shown that CDSA can be extended to BCP micelles with a conjugated crystalline polythiophene core 22,37 Electron microscopy. Bright-field transmission electron microscopy (TEM) images were taken using a Hitachi H-7000 instrument.…”
Section: Discussionmentioning
confidence: 99%
“…Many BCPs consisting of a long soluble block attached to a shorter crystallizable block 21 are potential candidates for this approach. While CDSA has been reported for BCPs with poly (3-hexylthiophene) 22 , polylactide 23 , polycaprolactone 24 and polyethylene 25 as the crystallizable block, one has the greatest control over this kind of seeded growth for polyferrocenylsilane (PFS) BCPs. Under appropriately chosen self-assembly conditions, all of the added unimer of a PFS BCP grow off the ends of the crystallite seeds in the sample, and uniform elongated structures can be formed [26][27][28][29][30][31] .…”
mentioning
confidence: 99%
“…[ 7,28,41 ] Herein, chloroform and acetonitrile were used as a good solvent for P3HT-b -P2VP and a selective solvent for P2VP, respectively. [ 23 ] A series of optical micrographs presented in Figure 1 a (see also Figure S1, Supporting Information) shows the progression of the formation of self-aggregates through the color change of solution (0.1 mg mL −1 of CP).…”
Section: P3ht-b -P2vp/qds Nws Formed By the Solution-biphase Methods Vmentioning
confidence: 99%
“…insulating blocks as for example PMMA (P3HT-b-PMMA), [224] or poly(2-vinylpyridine) (P3HT-b-P2VP, [225][226][227][228][229] or P4VP (P3HT-b-P4VP), [230][231][232] or PEO (P3HT-b-PEO), [233][234][235][236][237][238][239][240][241][242] or polylactides (P3HT-b-PLA), [243] or polyacrylic acids (P3HT-b-PAA). [244,245] Also more special block copolymer with P3HT block were reported as for example azobenzene liquid crystalline mesogen, 6-(4-((4-methoxyphenyl)diazenyl)phenoxy)hexyl methacrylate (MMAZO) incorporated into a block copolymer with P3HT.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%